Quantitative Security Risk Assessment of Enterprise Networks - Ou, Xinming; Singhal, Anoop; SpringerLink (Online service) (New York, NY : Springer New York, 2011)
Protection of enterprise networks from malicious intrusions is critical to the economy and security of our nation. This article gives an overview of the techniques and challenges for security risk analysis of enterprise networks. A standard model for security analysis will enable us to answer questions such as (3z(Bare we more secure than yesterday(3y (Bor (3z(Bhow does the security of one network configuration compare with another one(3y(B. In this article, we will present a methodology for quantitative security risk analysis that is based on the model of attack graphs and the Common Vulnerability Scoring System (CVSS). Our techniques analyze all attack paths through a network, for an attacker to reach certain goal(s).s
The Need for Quantifying Security -- Attack Graph Techniques -- The Common Vulnerability Scoring System (CVSS) -- Security Risk Analysis of Enterprise Networks Using Attack Graphs -- Conclusion.
Keywords: Computer science; Operating systems (Computers).; Computer Communication Networks; Computer system performance; Data protection; Computer Science; Systems and Data Security; Computer Communication Networks; Performance and Reliability; System Performance and Evaluation